Quantificação de Fases Cristalinas de Incrustações em Colunas de Produção de Petróleo pelo Método Rietveld - Lima, Daniel de Andrade (2009)
The scale is defined as chemical compounds from inorganic nature, initially soluble in salt solutions, which may precipitate accumulate in columns of production and surface equipment. This work aimd to quantify the crystalline phases of scale through the Rietveld method. The study was conducted in scale derived from columns production wells in development and recipients of pigs. After collecting samples of scale were performed the procedure for separations of inorganic and organic phase and preparation to be analyzed at the X-ray Laboratory. The XRD and XRF techniques were used to monitor whether identifying and quantifying crystalline phases present in the deposits. The SEM technique was used to visualize the morphology of the scales and assess their homogeneity after the milling process. XRD measurements were performed with and without milling and with or without the accessory spinner. For quantify crystalline phases the program DBWStools was used. The procedure for conducting the first refinement was instrumental in setting parameters, then the structural parameters of the phases in the sample and finally the parameters of the function profile used. In the diffraction patterns of samples of scale observed that the best measures were those that passed through the mill and used the accessory spinner. Through the results, it was noted that the quantitative analysis for samples of scale is feasible when need to monitor a particular crystalline phase in a well, pipeline or oil field. Routinely, the quantification of phases by the Rietveld method is hardwork because in many scale was very difficult to identify the crystalline phases present